Effect of injection timing on the exhaust emissions of a diesel engine using diesel-methanol blends - SAYIN, CENK; GÜMÜŞ, METİN (PERGAMON-ELSEVIER SCIENCE LTD, 2009)
Environmental concerns and limited resource of petroleum fuels have caused interests in the development of alternative fuels for internal combustion (IC) engines. For diesel engines, alcohols are receiving increasing attention because they are oxygenated and renewable fuels. Therefore, in this study, the effect of injection timing on the exhaust emissions of a single cylinder, naturally aspirated, four-stroke, direct injection diesel engine has been experimentally investigated by using methanol-blended diesel fuel from 0% to 15% with an increment of 5%. The tests were conducted for three different injection timings (15 degrees, 20 degrees and 25 degrees CA BTDC) at four different engine loads (5 Nm, 10 Nm, 15 Nm, 20 Nm) at 2200 rpm. The experimental test results showed that Bsfc, NOx and CO2 emissions increased as BTE, smoke opacity, CO and UHC emissions decreased with increasing amount of methanol in the fuel mixture. When compared the results to those of original injection timing, NOx and CO2 emissions decreased, smoke opacity, UHC and CO emissions increased for the retarded injection timing (15 CA BTDC). On the other hand, with the advanced injection timing (25 degrees CA BTDC), decreasing smoke opacity, UHC and CO emissions diminished, and NOx and CO2 emissions boosted at all test conditions. In terms of Bsfc and BTE, retarded and advanced injection timings gave negative results for all fuel blends in all engine loads. (c) 2008 Elsevier Ltd. All rights reserved.
Keywords: Diesel engine; Methanol; Emissions; Injection timing; COMBUSTION CHARACTERISTICS; PERFORMANCE; FUEL; ETHANOL; OIL